Analysis of ADRs with Hypokalaemia for Severity, Preventability and Causality in a Tertiary Care Centre in South India - Shiva Murthy Nanjundappa; Safeera Alikutty K; Mabel Kuriakose EV; Basalingappa Shivanna (Universitas Padjadjaran, Indonesia, 2023)
Hypokalemia is one of the most frequently seen electrolyte disturbances in clinical practice. Various drugs are known to induce hypokalemia, such as furosemide, thiazides, dicloxacillin, ampicillin, etc. The objective of this study is to assess hypokalemia adverse drug reactions (ADRs) for severity, preventability, and causality in a tertiary care centre in the southern part of India. It is a retrospective, cross-sectional study. Data collected at DMWIMS Medical College, India, as per the ongoing pharmacovigilance program of India from November 1st, 2016 to October 30th, 2017 (12 month period) was included for analysis in this study. The SADR form published by the Government of India under the PVPI program was used for collecting the data. In-patients who were on at least one medication and experienced hypokalemia ADR with or without other symptoms or signs were included. Both primary suspected drugs and concomitantly prescribed drugs were analyzed. For the assessment of ADRs, modified Hartwig and Siegel assessment scales and plasma K+ level criteria were used for severity, Schumock and Thornton criteria for preventability, the WHO-UMC scale, and Naranjo's algorithm for causality, respectively. Sixty hypokalemia ADRs were considered for analysis. Both genders were equally affected, with a mean age of 64.28 ± 3.02 years. Four groups of drugs were suspected to cause hypokalemia viz., anti-asthmatics (36.67 %), diuretics (31.67 %), antibiotics (18.33 %), and antidiabetics (13.33 Polypharmacy was reported in 43.33% of cases, with 4.40 ± 01.689 drugs prescribed on average. To summarize, hypokalemia is a preventable ADR and minor variations in serum K+ levels can have a negative impact on patients' outcomes and mortality. FDC of Levosalbutamol with Ipratropium Bromide was the most common causative agent suspected of causing hypokalemia. Elderly patients receiving one or more drugs that are known to alter K+ levels, need close monitoring, and correction of hypokalemia should be done to improve prognosis. Further studies are required to understand the mechanisms involved in DDIs and DDiIs to derive preventive strategies.